The Between-Competition Running Demands of Elite Hurling Match-Play - Brendan Egan; Damien Young; Kieran Collins; Shane Malone; Giuseppe Coratella (MDPI AG, 2021)
The current study aimed to investigate the differences in running demands between the National Hurling League (NHL) and the Championship, and within playing positions. GPS (10 Hz, STATSports Apex GNSS) were used to analyse the running demands during 34 games (2017-2020 seasons) of the Championship and the NHL. The running demands (total-, relative-, high-speed- [>17 km·h−1] and sprint [≥22 km·h−1] distance, number and length of sprints, and peak speed) were compared between competitions. Greater total- [ES = 0.32], relative- [ES = 0.26], and sprint-distance [ES = 0.41], and number of sprints [ES = 1.29] were completed in the Championship. The high-speed distance was similar between competitions. Half-backs and half-forwards covered greater total- (ES = 0.91 and 0.21, respectively), relative- (ES = 1.14 and 0.68, respectively), high-speed- (ES = 0.69 and 0.44, respectively), and sprint-distance (ES = 0.50 and 1.26, respectively), number of sprints (ES = 2.66 and 1.73, respectively), and peak speed (ES = 1.09 and 1.32, respectively) in the Championship. There was no difference (p < 0.05) in the sprint distance covered between positions in the Championship. The results showed that the Championship is more physically demanding. The findings present key implications for the transition between competitions.